1997
DOI: 10.1076/ejom.35.2.117.13067
|View full text |Cite
|
Sign up to set email alerts
|

On the Development of Cetacean Extremities: II. Morphogenesis and Histogenesis of the Flippers in the Spotted Dolphin (Stenella attenuata)

Abstract: Externally, the flippers of Cetacea resemble fish fins, but their internal structure is entirely mammalian. They show, however, some adaptative deviations from the typical pattern of the mammalian extremities, the most striking of which is an increased number of phalanges. The aim of this study is to describe the course of the development of flippers in the spotted dolphin (Stenella attenuata) and compare its features with other similar species from an evolutionary perspective. Early stages of flipper developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…Kü kenthal (1893) hypothesized the loss of digit III based on the presence of cartilaginous remnants in the shape of phalanges (histology of these elements showed they were cartilaginous and surrounded by connective tissue) and two branches of the radial nerve, instead of a single nerve, between the middle two digits in multiple specimens of balaenopterids (Table 1). This hypothesis has been accepted by several contemporary researchers (i.e., Barnes and McLeod, 1984;Sedmera et al, 1997;Kato, 2002;Aguilar, 2002) and was supported by similar findings of cartilage remnants in two specimens of fetal balaenopterids (Burfield, 1920). However, Howell (1930) believed Kü kenthal's (1893) hypothesis was flawed and that he misidentified metacarpal I as a prepollex and that specimens with the cartilage remnants were likely pathological.…”
mentioning
confidence: 58%
“…Kü kenthal (1893) hypothesized the loss of digit III based on the presence of cartilaginous remnants in the shape of phalanges (histology of these elements showed they were cartilaginous and surrounded by connective tissue) and two branches of the radial nerve, instead of a single nerve, between the middle two digits in multiple specimens of balaenopterids (Table 1). This hypothesis has been accepted by several contemporary researchers (i.e., Barnes and McLeod, 1984;Sedmera et al, 1997;Kato, 2002;Aguilar, 2002) and was supported by similar findings of cartilage remnants in two specimens of fetal balaenopterids (Burfield, 1920). However, Howell (1930) believed Kü kenthal's (1893) hypothesis was flawed and that he misidentified metacarpal I as a prepollex and that specimens with the cartilage remnants were likely pathological.…”
mentioning
confidence: 58%
“…These illustrations also indicate that phalangeal number increases with age, contrary to the observations of Kü kenthal (cited in Howell, 1930). Sedmera et al (1997) compare the hyperphalangy of cetaceans with that of ichthyosaurs, although they fail to mention several important morphological differences between the flippers of the two groups. Each digit in cetaceans is separated from the adjacent digit by blubber and dense fibrous connective tissue, while there are extensive interdigital phalangeal articulations in ichthyosaurs.…”
Section: Modifications Of Perichondral Ossificationmentioning
confidence: 97%
“…There are no delta-shaped bones associated with the supernumerary digit in P. sinus. Sedmera et al (1997) describe the development of the flipper in fetal Stenella attenuata. While they do not observe any delta-shaped bones, their illustrations do show that metacarpals 1 and 5 begin as ovoid centers of ossification, while metacarpals 2, 3, and 4 have concave longitudinal borders at the earliest examined stage.…”
Section: Modifications Of Perichondral Ossificationmentioning
confidence: 99%
“…Another unique morphological feature in the manus of cetaceans is hyperphalangy (Figure 1) (Howell, 1930;Sedmera et al, 1997;Richardson & Oelschläger, 2002;Fedak & Hall, 2004). Recent descriptive embryological studies of the pantropical spotted dolphin (Stenella attenuata) found that hyperphalangy was generated due to the terminal addition of phalanges well into the fetal stages, indicative of a delayed offset (heterochrony) or developmental continuation of digital development (Richardson & Oelschläger, 2002).…”
Section: Introductionmentioning
confidence: 99%